Design and analysis of miniaturized low profile and second-order multi-band polarization selective surface for multipath communication application - Wang, Hui; Zheng, Lin; Yan, Mingbao; Wang, Jiafu; Qu, Shaobo; Luo, Ruitao (Institute of Electrical and Electronics Engineers, 2019)
In this paper, a novel frequency selective surface (FSS) is designed; it has the characteristics of the low profile, second-order, multi-band, and the remarkable polarization selection properties. In the following, such an FSS having polarization selection characteristics will be referred to simply as a polarization selection surface (PSS). In a specific frequency band, the proposed PSS has a second-order selective transmission characteristic for TE and TM waves. Based on the coupling resonance filtering mechanism, the proposed PSS is composed of three metallic layers separated by two layers of dielectric substrates, which serves as the spatial form of the second-order microwave filter. The proposed PSS uses a sub-wavelength periodic structure array consisting of a non-resonant unit, and the unit size and the period within the range of 0.08λ 1 -0.15λ 1 , where the λ 1 =40.76 mm is the first passband wavelength of free space, so the PSS miniaturization characteristic is remarkable. The theoretical analysis and measure results show that the proposed bandpass PSS has good second-order polarization selection characteristics, out-of-band suppression level, and the flat transmission band, compared with the first-order bandpass PSS. In the range of incident angle of 0°-60°, it has a stable frequency response. It provides a reference for the design of a polarization wave generator and a polarization separation structure in a multipath communication system. © 2019 IEEE.